2011
DOI: 10.1590/s0006-87052011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant density and proportion on the interaction between wheat with alexandergrass plants

Abstract: Determination of competitive relationships among plant species requires appropriate experimental designs and method of analysis. The hypothesis of this research was that two species growing in coexistence show different growth and development due to their relative competitiveness. This research aims to measure the relative competitiveness of wheat crop compared to Alexandergrass by the interpretation of plant density and proportional effects using replacement series experiments. Monocultures were cultivated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Thus, initial development characteristics of each cultivar are crucial, and it is in the growing season that the definitive relationships of competition are generally set out (Lamego et al, 2005). Carvalho et al (2011), in a study of wheat and plantain signalgrass (Urochloa plantaginea), have shown that plantain signalgrass was more sensitive to intraspecific competition than wheat, and uncompetitive when compared to wheat. Wandscheer et al (2013) have shown that soybeans have a competitive ability equivalent to that of Indian goosegrass (wiregrass, crowfootgrass) (Eleusine indica).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, initial development characteristics of each cultivar are crucial, and it is in the growing season that the definitive relationships of competition are generally set out (Lamego et al, 2005). Carvalho et al (2011), in a study of wheat and plantain signalgrass (Urochloa plantaginea), have shown that plantain signalgrass was more sensitive to intraspecific competition than wheat, and uncompetitive when compared to wheat. Wandscheer et al (2013) have shown that soybeans have a competitive ability equivalent to that of Indian goosegrass (wiregrass, crowfootgrass) (Eleusine indica).…”
Section: Resultsmentioning
confidence: 99%
“…Interference of Sorghum sudanense and Eleucine indica in ... Several papers that aimed at evaluating the competitiveness between species showed that the more competitive one suffers more with intraspecific competition than with interspecific competition, because plants with greater competitive ability usually harms themselves due to lack of space or environmental resources (Carvalho et al, 2011;Dal Magro et al, 2011;Yamauti et al, 2011).…”
Section: Resultsmentioning
confidence: 99%